Mocaf flour, moringa flour, and mackerel flour food bars as an emergency food source for neurodivergent/autistic children during a natural disaster - Viorafanti Olivia Monica; Crosita.O Yessi; Malkan Bakhrul Ilmi Ibnu; Nasrullah Nanang (BIO Web of Conferences)
Indonesia is highly prone to natural disasters, when it strikes it often limits access to safe food for autistic children who require a gluten- and casein-free diet. This study aims to determine the optimal emergency food bar formulation suitable for autistic children, using mocaf flour, mackerel flour, and moringa leaf flour. This research used mocaf flour (25g (F1), 27g (F2), 29g (F3)), mackerel flour (5g (F1), 3g (F2), 1g (F3)), and moringa leaf flour (9g for all formulations). Proximate content was analyzed using AOAC 2012 and 2005 methods. The study employed a complete randomized design with two repetitions. Statistical analysis used for the proximate test was ANOVA and Duncan tests, while for sensory evaluation used Kruskall-Wallis and Mann-Whitney test. The best formulation was identified using the exponential method. The results showed that the food bars generally met emergency food standards, except for moisture content. ANOVA indicated no significant effect of formulation variation on moisture content (p=0.07). However, significant effects were observed on ash content (p=0.029), protein (p=0.001), and carbohydrate (p=0.003), but not on fat content (p=0.087). Sensory analysis revealed significant differences in all preference parameters. The best formulation, F3, provided 54% carbohydrates, 32.7% fat, and 8.31% protein, totaling 389.59 kcal per 100 grams.